The Effect of Corporate Governance Attributes on Corporate Social Responsibility Disclosure in Iraqi Companies: A Literature Review - Idan, Hayder Zghair; Rapani, Nor Hanani Ahamad; Khalid, Azam Abdelhakeem; Al-Waeli, Abbas Jumaah (The journal of contemporary issues in business and government, 2021)
This paper reviews and analyses 41 empirical studies examining the effects of internal corporate governance attributes on the disclosure of Corporate Social Responsibility (CSR) information by companies in Iraq. The inductive approach used in this paper entails the surveying, studying, comparing and summarizing of all papers published in prominent journals in the past seven years. By reviewing 41 empirical studies, this current study obtained mixed results ranging from Positive and negative statistically significant to statistically insignificant relationships, depending on the CSRD measures, sample selection and corporate governance attributes. The researchers also found that CG and CSR disclosure have a more positive relationship (57.80 %) than Negative and significant relationship (15.47%). However, the study found that (26.73%) an insignificant relationship .This paper also found that CSRD is weak in Iraq compared to developing countries in the analyzed studies. In the case of the Iraqi companies, Board of directors and managerial ownership were found to have a positive effect on the growth of social costs. As for the other variables, the study failed to discover any effects. In addition, the researchers also found that none of the previous studies had addressed the abovementioned correlation in the context of Iraqi companies.